Quantum metrology with entangled spin-coherent states of two modes - Ooi, Chong Heng Raymond; Berrada, K.; Khalek, S.A. (American Physical Society, 2012)
Recently, Gerry et al. [Phys. Rev. A 79, 022111 (2009)] studied the violation of the Bell-Clauser-Horne-Shimony-Holt inequality for two-spin systems, prepared in an entanglement of spin-coherent states, the so-called entangled spin-coherent states (ESCSs), and found maximal violations for a large class of states. In this paper, using the Holstein-Primakoff realization (HPR) of angular momentum algebra, we present an improved phase estimation scheme employing ESCSs and demonstrate that increasing the spin number gives the smallest variance in the phase parameter in comparison to NOON states under perfect and lossy conditions. The phase sensitivity of this interferometric scheme with parity detection on one of the output states is discussed.